Frequency of Metabolic Syndrome in Patients of Acute ST Segment Elevation Myocardial Infarction (Medical Forum Monthly, 2024)
Objective: To determine the frequency of metabolic syndrome (MS) in patients with acute ST segment elevation myocardial infarction (STEMI).Study Design: Cross-Sectional study.Place and Duration of Study: This study was conducted at the Department of Cardiology, Bahawal Victoria Hospital (BVH), Bahawalpur from March 2018 to tAugust 2018.Materials and Methods: A total of 380 patients, in the age range of 30 –70 years with Acute STEMI were included in the study. Only the patients fulfilling the inclusion criteria were included in the study. In this study, five components of MS were assessed after the written consent of the patients using the standard state of the art techniques.Results: Statistical analysis reveals that patients 47.36% were between 51 to 60 years of age with male to female ratio of 2:1. MS was found in 43.42% patients with 42.0% male and 46.15% female patients and incidence were increasing with passing years. The mean waist circumference was 89.12±6.43 in males and 93.23±11.65 in females, mean serum triglycerides was 146.11±27.77 in males and 148.66±28.54 in females, mean serum HDL Cholesterol was 41.17±6.32 in males and 50.94±4.55 in females, mean systolic blood pressure was 130±10 in males and 120±10 in females and mean diastolic blood pressure was 90±5 in males and 80±10 in females, mean fasting blood sugar was 114.11±15.76 in males and 108.56±20.43 in females.Conclusion: This study concludes that there is a high frequency of metabolic syndrome (MS) in acute STEMI patients in our population with hypertension and diabetes mellitus as the major components of MS.